Price Setting Behavior in Turkish Industries: Evidence From Survey Data - Saygin Sahinoz; Bedriye Saracoglu (Turkish Economic Association, 2008)
This study investigates the price setting behavior of Turkish industries based on the results of a survey that was conducted by the Central Bank of the Republic of Turkey. The results show that under normal conditions, the majority of the firms follow time-dependent pricing rule but when significant events occur substantial fraction of them alter their behavior to state dependent reviewing. The median Turkish firm reviews its prices every month, but changes its prices four times a year. Price reviews and changes are affected by: the market share, price discrimination, customer type, firm size and the existence of regulated prices.
Keywords: E30; D40; 330; price-setting; price-rigidity; survey; Betriebliche Preispolitik; Preisrigidität; Türkei